Measurement of constant radius swept features in cultural heritage. Issue 1 (1st April 2022) - Di Angelo, L.; Di Stefano, P; Morabito, A.E.
Abstract: The dimensional characterization of archaeological fragment is a very complex operation and could prove to be useful for identifying the presence of standard attributes in the ceramics found from a specific archaeological site, or for making comparisons and analysis of similarities or for studying ancient technologies used for manufacture of objects. The dimensional analysis of the fragments is now carried out manually with traditional measuring devices. Typically, the results obtained are inaccurate and non-repeatable measurements. This paper focuses on the dimensional characterization of a specific geometric class of features: the constant radius swept features (called here CRS features). Several archaeological features, such as rims, bases, decorative motifs, processing marks and grooves are referable from a geometric point of view to the class of CRS features. These are detail features, which may be very interesting for the investigation of some aspects related to the historical-archaeological classification of the find. CRS features are often found on worn, damaged (e.g. chipped) or fragmented objects; they are frequently characterized, from a geometric point of view, by free form surfaces and by a limited cross sectional extension. In some cases, CRS features can be of axially symmetrical geometry: this occurs quite frequently in the case of archaeological pottery. For all these reasons, it is often difficult to apply traditional manual methods for the quantitative dimensional characterization of CRS features. This paper describes an original methodology for the measurement of CRS features acquired by scanning technologies. The algorithmic implementation of this methodology, consisting of a suitable processing of the feature nodes, allows to carry out automatically the dimensional characterization of the feature.